The rectal mucosal immune environment and HIV susceptibility among young men who have sex with men - Ackerley, Cassie G.; Smith, S. Abigail; Murray, Phillip M.; Amancha, Praveen K.; Arthur, Robert A.; Zhu, Zhengyi; Chahroudi, Ann; Amara, Rama R.; Hu, Yi-Juan; Kelley, Colleen F. (Frontiers in Immunology, 2022)
Young men who have sex with men (YMSM) represent a particularly high-risk group for HIV acquisition in the US, despite similarly reported rates of sexual activity as older, adult MSM (AMSM). Increased rates of HIV infection among YMSM compared to AMSM could be partially attributable to differences within the rectal mucosal (RM) immune environment associated with earlier sexual debut and less lifetime exposure to receptive anal intercourse. Using an ex vivo explant HIV challenge model, we found that rectal tissues from YMSM supported higher levels of p24 at peak viral replication timepoints compared to AMSM. Among YMSM, the RM was characterized by increased CD4+ T cell proliferation, as well as lower frequencies of tissue resident CD8+ T cells and pro-inflammatory cytokine producing CD4+ and CD8+ T cells. In addition, the microbiome composition of YMSM was enriched for anaerobic taxa that have previously been associated with HIV acquisition risk, including Prevotella, Peptostreptococcus, and Peptoniphilus. These distinct immunologic and microbiome characteristics were found to be associated with higher HIV replication following ex vivo challenge of rectal explants, suggesting the RM microenvironment of YMSM may be uniquely conducive to HIV infection.